Development of Palliative Care Holistic Manual Guidelines Based on Islamic Psychospirituality - Chik, Hasimah; Saari, Che Zarrina; Syed Muhsin, Sharifah Basirah; Zainuddin, Sheriza Izwa; Munsoor, Mohamed Safiullah (Afkar: Jurnal Akidah dan Pemikiran Islam, 2025)
Palliative care is an approach that aims to improve the quality of life for patients and their families facing problems related to life-threatening illnesses. This article aims to study the expert consensus on the necessary elements that should form part of the manual guideline of care for palliative patients from an Islamic perspective. A discussion is outlined on the application of Islamic psychospiritual knowledge in building patient resilience to improve their quality of life. The methodology applied in this research was a combination of qualitative and quantitative approaches, utilising the design and development research (DDR) approach by Richey and Klein. Literature study was used to develop the Islamic Psychospiritual manual for holistic care. The research began with the first phase, known as need analysis, which involved administering a questionnaire to assess the need for this manual among patients and caregivers. The second phase involved manual development through expert discussion, and a set of questionnaires was subsequently administered to experts to test the usability of the manual for the third phase of DDR. The results of the study were analysed using the Fuzzy Delphi Method. The findings demonstrate that all items listed as elements of healthcare needs-namely, physical, psychological, spiritual, emotional, social, and logistical-are accepted and essential for improving patient endurance. The results of this study provide relevant information and guidelines in the manual for health service providers and parties involved in caregiving, aiming to optimise aspects of care for patients. In addition, the results of this study can provide information to non-governmental organisations in the provision of social volunteer services to help patients deal with the difficulties of health challenges. This study highlights the importance of holistic care in enhancing the quality of life for patients. The manual guidelines that have been developed can be used by all categories of caregivers to improve the quality of life. This manual was included with the guidelines highlighted by Islam regarding faith, worship, and akhlaq during times of pain and struggle to achieve well-being in life.